2021
DOI: 10.1039/d1dt00152c
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity of an inorganic glass melt with ZIF-8

Abstract: The thermal behaviour of ZIF-8, Zn(meIm)2 in the presence of a sodium fluoroaluminophosphate glass melt was probed through differential scanning calorimetry and thermogravimetric analysis. The structural integrity of ZIF-8 was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…[41] A recent example of a MOF-CIGC involved the combination Suitable thermal compatibility was rationalised, given that the T g of the glass (352 °C) was much lower than the T d for ZIF-8 (520 °C). [42] Varying amounts of ZIF-8 were used and 450 °C was selected as the working temperature because it was between the inorganic glass T g and the T d of ZIF-8. However, analysis on the synthesised composites suggested that although some interaction had occurred between the inorganic glass and ZIF-8, this resulted in partial destruction of the ZIF-8 component.…”
Section: Mof Crystal-inorganic Glass Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] A recent example of a MOF-CIGC involved the combination Suitable thermal compatibility was rationalised, given that the T g of the glass (352 °C) was much lower than the T d for ZIF-8 (520 °C). [42] Varying amounts of ZIF-8 were used and 450 °C was selected as the working temperature because it was between the inorganic glass T g and the T d of ZIF-8. However, analysis on the synthesised composites suggested that although some interaction had occurred between the inorganic glass and ZIF-8, this resulted in partial destruction of the ZIF-8 component.…”
Section: Mof Crystal-inorganic Glass Compositesmentioning
confidence: 99%
“…A recent example of a MOF‐CIGC involved the combination of a sodium fluoroaluminophosphate glass series, 78 %([Na 2 O] 1.6 [P 2 O 5 ])–22 %([AlO 1.5 ][AlF 3 ] 0.7 ) with ZIF‐8 [Zn(mIm) 2 ]. Suitable thermal compatibility was rationalised, given that the T g of the glass (352 °C) was much lower than the T d for ZIF‐8 (520 °C) [42] . Varying amounts of ZIF‐8 were used and 450 °C was selected as the working temperature because it was between the inorganic glass T g and the T d of ZIF‐8.…”
Section: Classification Of Mof‐glass Compositesmentioning
confidence: 99%
“…In general, inorganic glasses avoid crystallization either by having complex chemical compositions, also called “principle of maximum confusion”, or by kinetically frustrating the crystallization process by cooling the melt beyond its critical cooling rate . They are relatively cheap and well-studied materials, though they are almost completely unexplored as host materials for crystalline MOFs. , No example of successful crystalline MOF–inorganic glass composite formation is known to the authors at the time of writing. Exploring this class of composites, together with the need to improve MOF mechanical properties and reduce their costs, is the motivation for this work.…”
Section: Introductionmentioning
confidence: 99%
“…13 They are relatively cheap and well-studied materials, though they are almost completely unexplored as host materials for crystalline MOFs. 14,15 No example of successful crystalline MOF− inorganic glass composite formation is known to the authors at the time of writing. Exploring this class of composites, together with the need to improve MOF mechanical properties and reduce their costs, is the motivation for this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 They are relatively cheap and well-studied materials, though they are almost completely unexplored as host materials for crystalline MOFs. 14,15 No example of successful composite formation is known to the authors at the time of writing.…”
Section: Introductionmentioning
confidence: 99%